MODERN APPROACHES AND METHODS OF TEACHING FOREIGN LANGUAGES IN COLLEGES - Ткаченко, Н.; Мостицька, Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The importance of a foreign language in the training of students in colleges is considered; the necessity of language proficiency as an important component of the formation of modern personality is analyzed. The necessity of systematization of existing and formulation of new provisions on the definition of trends, features and future directions of development of vocational education. The modern concepts and methods of teaching a foreign language, as well as their application in the work of circles to study the culture of English-speaking countries in the after-hours, which will quickly and efficiently learn English. The aim of the article is to analyze the actual problems of teaching a foreign language in colleges by determining the possibility of applying modern and promising concepts of teaching a foreign language, as well as teaching methods in the development of vocational education. Three different approaches to learning a foreign language that can be used in the study of a foreign language during the work of the circle of foreign language "English-speaking culture experts" are analyzed. This circle is the main form of implementation of creative activity of students in the study of a foreign language outside school hours. The combination of purposeful development of communication skills and the concept of "First meeting" allows you to fully take into account the specifics of teaching a foreign language as a subject and provide a link between the content and quality of the study of this subject during the entire period of study in College. The basic methods of teaching foreign languages in colleges, including after-hours in the organization of group work. The choice of the correct method of training will ensure the efficient results of the study of foreign languages in colleges according to the pressing challenges of our time. It is proposed to use the method of scenario (Storyline Method) and the method of project learning, which will provide a projected increase in the number of students who are engaged in scientific and research work, the formation of students' skills in working with information materials, the development of observation, visual memory, imagination, associative thinking, improving the quality of knowledge, skills in science and foreign language